Valuing crop biodiversity [ on-farm genetic resources and economic change - Smale, Melinda (CABI, 2006)
In agricultural systems, diversity of crops and varieties is essential to combat the risks farmers face from pests, diseases and variations in climate. Crop biodiversity also underpins the range of dietary needs and services that consumers demand. Thereis growing concern, however, about declining diversity of crop genetic resources on farms, associated with social and economic change. This book contributes to a better understanding of the challenges involved in maintaining local crop biodiversity within a rapidly changing global food system. It provides empirical studies, applying economic tools and methods for valuing and managing crop biodiversity on farms. The book is divided into five sections: (1) introduction (1 chapter); (2) private value: stated preference of farmers (3 chapters); (3) private value: revealed preferences of farmers (5 chapters); (4) public values, villages and institutions (7 chapters); and (5) conclusions (2 chapters). This book will interest agricultural and resource economists, applied researchers working in international and national organizations and projects, as well as scientists involved in local plant breeding and genetics.